Speech language characteristics and intervention approaches in lockedin syndrome post snake envenomation - Arya, Shantanu; Vaid, Dakshta; Zangmo, Nima; Garg, L. N.; Kumar, Sachin Praveen (International Journal of Research in Medical Sciences, 2020)
The present case study illustrates hypoxic-ischemic encephalopathy as a result of neuroparalytic snake envenomation in an 11 year old male patient. Detailed speech assessment was done which revealed diverged oral structures and language loss. The study aims to document speech and language characteristics as well as rehabilitation in terms of speech therapy. The study enlightens the role of speech language pathologist in assessment and intervention of locked in syndrome. Study shows the swapped roles of traditional therapy approaches and the importance of augmentative and alternative communication as compassion and a beneficial technique in an intricate incident like hypoxic-ischemic encephalopathy as a result of neuroparalytic snake envenomation.